Diversifying sources of income for terrorist organizations: ISIS terrorist organization of 2014-2021 as a model: the international and political journal - م. د علاء عبيس راضي الجبوري; م. م آيات احمد سلمان (The International and Political Journal, 2025)
he terrorist organization Islamic State in Iraq and Syria (ISIS) realized the importance of funding from the first moment of its establishment as an organization seeking to establish its alleged state. Even before that, when it was under previous names (the Islamic State in Iraq) in order to carry out various activities that achieve its goals, although they differed from one period to another and according to the vision of the organization's central leadership. The importance of funding has increased since 2013 when the official announcement of the establishment of the desired Islamic Caliphate was made. Funding was not limited to salaries for members of the organization or carrying out terrorist operations or running daily affairs, but rather it emerged more prominently in the issue of enticement for the recruitment process, which distinguished the organization from other organizations.The organization initially tried, through traditional financial networks, to finance all its activities, especially during the period of empowerment and control over the land, i.e. in light of the actual caliphate on the ground. It relied on oil and gas fields, tributes, extortion, agriculture, and obtaining funds from Iraqi bank branches and others. The organization continued in this manner until it declined and was militarily defeated. These sources were no longer sufficient, or some of them were not present at all, which prompted the organization, through its leadership, to think of other sources through which it could finance its activities, especially paying salaries. After the divisions that occurred within its ranks, and the restrictions imposed on it by some countries in its main strongholds, it turned to modern sources, sometimes with traditional ones, and sometimes as an alternative to them. These sources, due to their advantages, provided a large financial abundance for the organization. What cryptocurrencies, social media, the change in financial concentration locations, drugs, and other funds provide, enabled the organization to continue despite the military defeat it suffered in Iraq, Syria, and some other countries in which it is present. Many countries sought to confront the organization financially through policies, procedures, conferences, and agreements in order to stop the organization from using them, and although they achieved some of that, they were not sufficient to stop the funding, which requires more efforts from them, especially in the matter of non-traditional sources that are difficult to control.